Teacher training in Nature Sciences for rural schools in the UFFS - Campus Erechim: perspectives and challenges - Moises Marques Prsybyciem; Almir Paulo dos Santos; Jerônimo Sartori (Universidade Federal do Norte do Tocantins, 2017)
This work aims to highlight the perspectives and challenges encountered in the initial training of teachers in the Interdisciplinary Course in Rural Education: Natural Sciences - Bachelor of the Federal University of the Southern Frontier, Campus Erechim, for schools in the countryside. This bibliographic and documentary research is of an exploratory nature, whose approach was of the qualitative type. The main results highlight the challenges and potentialities of teacher training for schools located in indigenous communities and schools in the countryside, as well as their articulation with the Teaching of Natural Sciences (Chemistry, Physics and Biology), such as: identity Cultural diversity of the subjects, the clash of cultures (different rural people and different specificities), pedagogical aspects related to organization and work in the alternation regime. These elements point to a teacher profile graduated in a Rural Education Degree that needs to understand the cultural, ideological, social, political, scientific, technological, ethical and economic contradictions faced by subjects living in and out of the field. These results show the need to broaden the discussions on Science and Technology and its social implications, aiming to strengthen the identity and culture of the field that is its own.